MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI PENGGUNAAN MEDIA UTAP PADA PEMBELAJARAN IPAS DI KELAS V SDN 07 BATUDAA PANTAI KABUPATEN GORONTALO - Idris Sanabi; Fandi H. Binggo; Yusraningsih Pongoliu (Jurnal Ilmu Pendidikan UMGo, 2025)
Learning outcomes are an important indicator of the success of the learning process, especially in Natural and Social Sciences (IPAS) learning at elementary school. However, preliminary observation in grade V of SDN 07 Batudaa Pantai showed that students’ learning outcomes on the topic of harmony in ecosystems were still low because learning media were limited and classroom activities tended to rely on textbooks. This study aims to improve students’ learning outcomes through the use of UTAP media, a snakes-and-ladders-based instructional game adapted to IPAS learning. This research employed Classroom Action Research (CAR) consisting of planning, action, observation, and reflection. The participants were 15 fifth-grade students of SDN 07 Batudaa Pantai, Gorontalo Regency. Data were collected through learning outcome tests, observation of teacher and student activities, and documentation, and were analyzed using descriptive percentage analysis. The results showed that students’ learning outcomes increased from 40% in the preliminary observation to 73.4% in Cycle I and 86.7% in Cycle II. The use of UTAP media encouraged students to become more active, motivated, and involved in group discussion and question-answer activities. These findings indicate that UTAP media can create a more interactive and enjoyable learning atmosphere, support students’ understanding of ecosystem concepts, and improve learning outcomes in IPAS learning. Therefore, UTAP media can be considered an effective alternative instructional medium for elementary school learning.